2021
DOI: 10.1111/maps.13753
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and importance of petrological type 1 chondritic material

Abstract: We review the mineralogy, petrology, and abundance of petrological type 1 extraterrestrial material. Such material has been completely altered by aqueous processing on its parent bodies. As well as the four meteorite groups that contain type 1 members (CI, CM, CR, and CY), we summarize data from the 2019 fall Flensburg and a recent reanalysis of the "meteorite" Bench Crater found on the Moon, along with fine-grained micrometeorites, interplanetary dust particles, and xenoliths in meteorites. Type 1 materials e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 199 publications
(299 reference statements)
0
7
0
Order By: Relevance
“…A total of 5.4 grams of surface and subsurface materials of the C-type asteroid 162173 Ryugu were collected by the Hayabusa2 spacecraft during its two touchdowns and then brought back to Earth on December 5 th , 2020. Initial characterization of these fragments at the JAXA curation facility revealed that Ryugu materials mineralogically resemble those of CI (Ivuna-type) chondrites 1,2 , an extremely rare meteorite group in our collections 11 . From a chemical perspective, CI chondrites are among the most primitive meteorites, having a bulk composition similar to that of the solar photosphere (e.g., ref 12,13 ).…”
Section: Full Textmentioning
confidence: 94%
See 1 more Smart Citation
“…A total of 5.4 grams of surface and subsurface materials of the C-type asteroid 162173 Ryugu were collected by the Hayabusa2 spacecraft during its two touchdowns and then brought back to Earth on December 5 th , 2020. Initial characterization of these fragments at the JAXA curation facility revealed that Ryugu materials mineralogically resemble those of CI (Ivuna-type) chondrites 1,2 , an extremely rare meteorite group in our collections 11 . From a chemical perspective, CI chondrites are among the most primitive meteorites, having a bulk composition similar to that of the solar photosphere (e.g., ref 12,13 ).…”
Section: Full Textmentioning
confidence: 94%
“…From a chemical perspective, CI chondrites are among the most primitive meteorites, having a bulk composition similar to that of the solar photosphere (e.g., ref 12,13 ). However, paradoxically, they also contain very high abundances of mineral phases (e.g., carbonates, magnetite, phyllosilicates, and sul de) produced by extensive interactions between water and the original mineralogy on their parent asteroids (e.g., refs 11,14 ). Despite having a solar-like bulk elemental composition, the CI chondrites are the furthest of all carbonaceous chondrite meteorites from the solar value in terms of oxygen isotopes (e.g., ref 15 ).…”
Section: Full Textmentioning
confidence: 99%
“…Analyses of the matrix areas were subjected to much higher 16 OH À signal than the olivine and pyroxene Note: Clasts with a C1 affinity are commonplace in the CMs but rarely recorded (Russell et al, 2022). a Kerraouch et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…As Pepin has shown in several reports, an extrapolation to a primitive reservoir using fission-corrected atmospheric Xe data and hydrodynamic fractionation models to obtain the primitive composition U-Xe (Table 2), that differs slightly from Xe-PR(-5), specifically in the case of isotope 124 Xe. Evolution of terrestrial Xe since Archean times, as proposed by Avice et al (2017Avice et al ( , 2018, or continuing accretion of Type I carbonaceous volatile-rich matter (Russell et al 2022) are possible explanations. Many relevant questions like timing and mechanisms of fractionation processes also require further investigations.…”
Section: Planetary Atmospheresmentioning
confidence: 96%
“…Now we consider another apparently novel Xe isotopic pattern reported by King et al (2019) in Yamato carbonaceous (CY) chondrites. These carbonaceous chondrites originate from a distinct parent body that shows a distinct and heavy oxygen isotopic signature on the terrestrial fractionation line (Russell et al 2022). King et al (2019) reported noble gas data, including Xe, and concluded that the CY samples show varying degrees of aqueous alteration and might present possible analogs for asteroid Ryugu.…”
Section: Mass Fractionationmentioning
confidence: 99%